Nano Topological Analysis For Power System Control - EL-Sayed, M.Kamel (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
In this paper,we introduce an approach for analysis of information concerning electrical power system. The suggested method is a result of hybridizing rough set concepts with nano topology constructed on the set of all data using the boundary of uncertain decision sets and its lower approximation. Bases of nano topologies are used as indicators for selecting effective features in information system of a power control. This method is applied using the main experimental data which make the suggested model near from the real life information.